Trend analysis of rainfall data Rangpur, Bangladesh - Saha, Sudip (International Journal of Advanced Geosciences, 2020)
The study area lies in Bangladesh that is in the tropical area. The analysis of rainfall data reveals that the average annual rainfall in Rangpur was 2099.25 mm that varies from 427 mm to 3748 mm within the investigated period of time. The highest amount of annual rainfall was recorded in 1984. Heavy rainfall occurs in the month of July of the year. The highest amount of total monthly rainfall was recorded in July, 1987 and measured as 1314 mm. The rainfall trend can be expressed as monsoon rainfall > pre-monsoon rainfall> post monsoon rainfall. The total amount of annual rainfall is strongly significantly positively correlated with the total monthly rainfall of the months of June, July August, September and October and significantly positively correlated with the total monthly rainfall of the month April. The analysis shows that it rained in every year in the month of June as the minimum monthly value for June is greater than zero. Pearson correlation index shows that the mean daily temperature is significantly negatively correlated with daily rainfall which implies that fall of daily mean temperature with the daily rainfall. The increasing trend of annual rainfall suggests the climate change in Rangpur within the investigated period of time. In Rangpur, the value of skewness for all rainfall data are positive that indicate the data are skewed to the right. The positive values of kurtosis indicate that the distribution is not normal. Â